Indonesian Foreign Policy Maintaining In Maritime Security Towards China’s New Silk Road - Gizem Butun; Yanyan Mochamad Yani; Arry Bainus (Universitas Komputer Indonesia, 2021)
Indonesian Maritime Domain has overlapping area with one of the immense project which is China’s New Silk Road. Thus, with providing opportunities such as financial loans and infrastructure investment which are essential to realize the appealing policy of Joko Widodo’s, Global Maritime Fulcrum. However, this project doesn’t seem without implications for Indonesian Maritime Security given current unsolved problems, South China Sea Dispute, IUU fishing and Natuna island. Indonesian Foreign Policy has always been on one of the main policy which is Free and Active. Also, internal and external factors such as anti-Chinese sentiment and US-China rivalry have been determinative for Joko Widodo’s Policy as well. The researcher used the Qualitative research method with an explanatory approach in conducting the research and processing the data. The primary data document directly from ministries as an official statement and speech of leaders. Secondary data, written and visual sources such as scientific books or journals, archival sources, personal documents, internet sources, other official documents. This research concluded that Indonesian Foreign Policy is crucial in order to obtain benefits while reducing implications. Therefore, this research sought to establish how Indonesian Foreign Policy has been managing China’s New Silk Road to maintain Maritime Security of Indonesia. Keywords : Foreign Policy, Maritime Security, Silk Road